Influence of Soil Tillage Systems and Weed Control Treatments on Root Nodules, Production and Qualitative Indicators of Soybean. (2016) - Chetan, Cornel; Rusu, Teodor; Chetan, Felicia; Simon, Alina
Abstract: The use of herbicides increases labor productivity being synthetic products, foreign ecosystem, abused, without a thorough knowledge can be dangerous for the environment through the introduction of toxic waste in agricultural ecosystems. It is necessary to reduce the doses used in relation to the use of conservative technology, finding solutions optimized for effective weed control. Research conducted at Agricultural Research and Development Station Turda in the years 2013 and 2014 have followed the effect of 12 variants of herbicides used to control weeds in soybean crop, sown in two tillage systems (classical system and minimal tillage system), the formation of root nodules, soybean production and quality indicators. Tillage system significantly influenced both qualitative indices and soybean crop production (being 2635 kg/ha to the classical and 2131 kg/ha minimum tillage system). The significant influence of tillage soybeans in fat content (20.34% in minimum tillage system; 19.94% to the classical) and on protein (39.89% minimum tillage system; 40.56% in the classic).